Memes and the Moroccan Far-Right. (October 2021) - Moreno-Almeida, Cristina; Gerbaudo, Paolo
Facebook meme pages in the Middle East and North Africa (MENA) have flared-up in the past decade. Since 2017, some Moroccan pages have started sharing exclusively patriarchal, ultra- and ethnonationalist, misogynist, and racist content shaped to look in line with "alt-right" online aesthetics. Self-identifying as right-wing, these pages have memetized an entire ecosystem of scapegoats as enemies of the nation. Furthermore, they have rescued symbols from the past, such as the late King Hassan II or the Marinid flag, to formally establish the Moroccan Right. In view of this trend, this paper examines Moroccan Facebook meme pages that share ultranationalist content and build on a scapegoating strategy to understand how Far-Right ideologies have been adapted in the MENA. Through multimodal discourse analysis of memes posted since 2017 until April 2020, this paper studies the ways in which the revival of Far-Right tropes is contributing to reshaping local digital political landscapes and pushing toward an Arab Right. By examining a collection of over 1, 600 memes, our paper argues that this new online Moroccan Far-Right discourse is adapting Far-Right views, particularly in terms of gender and race, to local politics. This research contends that internet memes are effectively acting as an entry point in the creation of a Moroccan Far-Right. As a newly formed trend, however, the Moroccan Far Right is still negotiating its main tenets.